A pleiotropic mutation in Neurospora conferring sensitivity of analogues of amino acids, purines and pyrimidines - D. E.A. Catcheside (Fungal Genetics Reports, 1978)
A pleiotropic mutation in Neurospora conferring sensitivity of analogues of amino acids, purines and pyrimidines